Donation for students from the compound collections - Nor Salwana, Mohammad Idris (2020)
Pekan, 21 October 2020 - The Security Division, Universiti Malaysia Pahang (UMP), handed over a contribution of RM1,956 as part of the payment of compounds and fines due to violating traffic rules and road discipline on campus for students.